Gambaran Profil Lipid Pada Obesitas Perempuan - Nani Kurnaeni (Poltekkes Kemenkes Bandung, 2013)
Obesity and dyslipidemia are two risk factors for atherosclerosis that can lead to coronary heart disease risk factors. Measurement of lipid profiles in obese individuals as one test to see whether or not a person dyslipidemia. Lipid profile consisting of total cholesterol, triglycerides, HDL-C and LDL-C. The ratio of HDL-C with LDL-C is inversely related to the occurrence of atherosclerosis. HDL-C levels were significantly higher can provide protection against CHD, in contrast to LDL-C if the higher levels it will lead to atherosclerosis in the blood vessel walls that can increase the risk of CHD. The purpose of this study to describe the lipid profile in obese individuals. Descriptive research method used. The entire population of obese women in RW 17 Sub District Cibabat North Cimahi, samples used by 30 people. Data analysis was done by a percentage (%), descriptive statistics and correlation tests. Inspection methods for total cholesterol CHOD-PAP, GPO-PAP triglyceride, HDLC PTA precipitation, which results read using a photometer MicroLab 300 and LDL-C using the Friedwald formula. Of 30 obese women gained a mean total cholesterol level 229 mg/dL (164-293) mg/dL, triglycerides 158 mg/dL (56-417) mg/dL , HDL-C of 49.3 mg/dL (30.7-82.7) mg/dL and LDL-C 148 mg/dL (105-191) mg/dL. Based on age and BMI ranges mostly in the age range 55-69 years ; 16 people (53%) and BMI ranges from 27 to 29.9 ; 18 people (60%). Lipid profile picture 28 people who had dyslipidemia (93%). From the results of statistical tests of correlation between age and total cholesterol, triglycerides, HDL-C and LDL-C values obtained significant (0.109), (0.125), (0.373) and (0.142) > a means that there is no correlation between BMI and the levels total cholesterol, triglycerides, HDL-C and LDL-C values obtained significant (0.520), (0397 , (0761) and (0819) > a means that there is no correlation . In obese individuals who have dyslipidemia with elevated levels of total cholesterol, triglycerides and LDL-C and decreased HDL-C levels will further accelerate the process of atherosclerosis and CHD risk factors cause. For obese patients with dyslipidemia who are advised to do a lipid profile routine/regular consultation with the doctor and get treatment.